Determining seagrassess community structure using the Braun – Blanquet technique in the intertidal zones of Islas de Gigantes, Philippines - Quin Yudelmo Clarito; Nora O. Suerte; Elena C. Bontia; Ivy Maestrecampo Clarito (Sustinere: Journal of Environment and Sustainability, 2020)
The seagrass ecosystem which is considered the most productive ecosystem occurs in tropical and subtropical shallow marine waters where it supports diverse flora and fauna. Seagrasses of Islas de Gigantes, Carles, Iloilo were assessed to determine species diversity, abundance, canopy height and percentage cover. Braun – Blanquet technique was used where 3 transects were laid in each station in three barangays of Islas de Gigantes, namely: Barangay Asluman, Barangay Granada and Barangay Gabi. A total of 7 species were found, Thalassia hemprichii, Cymodocea rotundata, Cymodocea serrulata, Halodule pinifolia, Halodule uninervis, Enhalus acoroides and Syringodium isoetifolium. Using the Shannon Diversity Index, the seagrass bed in Gabi was the most diverse with a value of 2.8. Sorenson's coefficient (CC) was used to compute the species similarity attributes indicating that the three communities have many similarities to each other in terms of species diversity and environmental parameters that affect seagrass ecosystems. Syringodium isoetifolium had recorded the highest number of shoots (475 shoots/m2) in Granada. The percentage cover of seagrasses varied across the sampling sites ranging from 55% - 67.50%, with a mean value of 62.50%. However, E. acoroides had the tallest canopy height recorded that ranged from 12.33 – 24.83 cm.